The Effect of Google Classroom Media Utilization in Physics Learning on Students' Interest and Learning Outcomes at SMA Negeri 9 Kendari - La Isa; Santri Santri; Zainuddin zainuddin; La Ode Asmin; Dewi Santri (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2023)
This study aims to determine the effect of Google Classroom media utilization in learning Physics on students' interest and learning outcomes at SMA Negeri 9 Kendari. The method used in this research is an ex post facto survey with a quantitative approach. The data analysis technique used is path analysis with the help of Smart-PLS software at α = 5%. Based on the study results, it is concluded that the utilization of Google Classroom is classified in the excellent category with a percentage figure of 69.59%. Learning interest is organized in a strong class with a percentage rate of 75.55%. Learning outcomes are classified in the moderate category with an average acquisition value of 73.62 and a percentage rate of 100% of students meeting the minimum completeness criteria (KKM). Google Classroom utilization (X) significantly affects learning interest (Y1) by 0.559. Google Classroom utilization can explain/contribute to students' physics learning outcomes by 13%. Google Classroom utilization (X) has a significant indirect effect on learning outcomes (Y2) through learning interest (Y2) of 0.240. Google Classroom utilization can explain/contribute to students' physics learning outcomes.